The possible association between in vitro fertilization treatments and cancer development. Issue 1 (1st January 2003) - Lerner-Geva, L.; Geva, E.; Lessing, J. B.; Chetrit, A.; Amit, A.
Abstract : The objective of this paper is to assess whether ovarian hyperstimulation and in vitro fertilization (IVF) are associated with increased risk of cancer development, using an historical cohort analysis of infertile women who attended the IVF unit, Lis Maternity Hospital Tel Aviv Medical Center, Tel Aviv, Israel. One thousand and 82 women participated in the IVF treatment program between 1984 and 1992. Cancer incidence rates were determined through the National Cancer Registry and were compared to the expected rates with respect to appropriate age and continent of birth. Twenty-one cases of cancer were observed as compared to 11 that were expected (SIR 1.91; 95% CI 1.18–2.91). When cancer cases that were diagnosed within one year of the IVF treatment were excluded from the analysis (SIR = 1.46; 95% CI 0.83–2.36), no significant excess risk of cancer was noted. We conclude that in this cohort of infertile women, the higher than expected cancer rate could not be attributed to IVF treatments. Special attention should be made to women who may be diagnosed with cancer during or shortly after IVF treatment.